A Case of Acute Hepatitis E Infection in a Patient with Non-Hodgkin Lymphoma Treated Successfully with Ribavirin - Hasan N. Y. Haboubi; Rizwan Diyar; Ann Benton; Chin Lye Ch’ng (Case Reports in Gastrointestinal Medicine)
We present the case of a man who, following immunosuppressive treatment for non-Hodgkin lymphoma, became infected with viral hepatitis E. Acute hepatitis E virus infection should be considered in patients with deranged liver function on a background of haematological malignancies or immunosuppression, even without travel to endemic regions. Whilst clearance is usually spontaneous in immune-competent individuals, these at-risk groups may develop a more complicated and protracted disease course. Thus awareness is important as additional treatment with ribavirin or pegylated interferon may be required, as in this case, in order to help achieve eradication.